Statistical analysis and molecular docking study on halal potential antioxidant from anacardium occidentale fruits - Shuhaimen, Muhammad Shahrain; Abdullah, Erna Normaya; Omar, Muhammad Nor; Ahmad, Mohammad Norazmi (2018)
Lipids in foods are prone to oxidation that causes deterioration of food quality and formation of free radicals. Free radicals in food products can cause oxidative damage which could results in many chronic health diseases. Commercially available synthetic antioxidants used as food additives are reported to endanger health. Therefore, Halal natural antioxidants from plants are investigated. In this study, viscious liquid containing antioxidant properties was extracted from freeze dried cashew (Anacardium occidentale) apple using supercritical fluid extraction (SFE) with carbon dioxide (CO2) as the solvent. The extractions were optimized with response surface methodology (RSM) using the central composite rotatable design (CCRD). The effects of pressure (x1; 200-300 bars), time (x3; 30- 90 min), and temperature (x2; 30-50°C) were studied on the antioxidant activity of the liquid, measured using the DPPH inhibition assay. The statistical ana lysis was performed by ANOVA and the quadratic model obtained is significant (R2= 0.9858). Based on the RSM model, the optimal extraction conditions were obtained at 288.98 bar, 66.21 min, and 36.98°C that yields 70.3399% DPPH inhibition, which is in reas onable agreement with the validation test (n= 3) that yields the highest activity (71.5167±0.6684%). Based on the t-values, the ascending order of the effects of linearterms on cashew apple antioxidant activity was was temperature < time < pressure. The total phenolic content of the extract is 0.056 mg GAE/mL. The optimised extract was analysed using GC-MS and FT-IR for chemical compounds identification. Four prominent compounds were identified from the chromatogram. The antibacterial activity of the extract was tested against Gram-positive and Gram -negative bacteria. Molecular docking was used to study the interactions of the identified compounds from the extract with the bacteria.